Nanoceria provides antioxidant and osteogenic properties to mesoporous silica nanoparticles for osteoporosis treatment. (1st March 2021) - Pinna, Alessandra; Torki Baghbaderani, Mohammad; Vigil Hernández, Victoria; Naruphontjirakul, Parichart; Li, Siwei; McFarlane, Taneisha; Hachim, Daniel; Stevens, Molly M.; Porter, Alexandra E; Jones, Julian R.
Abstract: Osteoporosis, a chronic metabolic bone disease, is the most common cause of fractures. Drugs for treating osteoporosis generally inhibit osteoclast (OC) activity, but are rarely aimed at encouraging new bone growth and often cause severe systemic side effects. Reactive oxygen species (ROS) are one of the key triggers of osteoporosis, by inducing osteoblast (OB) and osteocyte apoptosis and promoting osteoclastogenesis. Here we tested the capability of the ROS-scavenger nanoceria encapsulated within mesoporous silica nanoparticles (Ce@MSNs) to treat osteoporosis using a pre-osteoblast MC3T3-E1 cell monoculture in stressed and normal conditions. Ce@MSNs (diameter of 80 ± 10 nm) were synthesised following a scalable two-step process involving sol-gel and wet impregnation methods. The Ce@MSNs at concentration of 100 μg mL −1 induced a significant reduction in oxidative stress produced by t-butyl hydroperoxide and did not alter cell viability significantly. Confocal microscopy showed that MSNs and Ce@MsNs were internalised into the cytoplasm of the pre-osteoblasts after 24 h but were not in the nucleus, avoiding any DNA and RNA modifications. Ce@MSNs provoked mineralisation of the pre-osteoablasts without osteogenic supplements, which did not occur when the cells were exposed to MSN without nanoceria. In a co-culture system of MC3T3-E1 and RAW264.7 macrophages, the Ce@MSNs exhibited antioxidant capability and stimulated cell proliferation and osteogenic responses without adding osteogenic supplements to the culture. The work brings forward an effective platform based for facile synthesis of Ce@MSNs to interact with both OBs and OCs for treatment of osteoporosis. Graphical abstract: Image, graphical abstract